Early blood-brain barrier permeability in cerebella of PLSJL mice immunized with myelin basic protein - Spitsin, Sergei (2008)
The blood-brain barrier (BBB) is dramatically but transiently compromised in the cerebella of myelin basic protein immunized mice at least one week prior to the development of the paralytic phase of experimental allergic encephalomyelitis (EAE). Treatment of mice with the peroxynitrite-dependent radical scavenger uric acid (UA) during the first week after immunization blocks the early increase in cerebellar BBB permeability and the subsequent development of clinical signs of EAE. These results indicate that the early loss of BBB integrity in the cerebellum is likely to be a necessary step in the development of paralytic EAE.